2015
DOI: 10.1590/2359-3997000000106
|View full text |Cite
|
Sign up to set email alerts
|

Atkins diet program rapidly decreases atherogenic index of plasma in trained adapted overweight men

Abstract: Background:The Atkins diet program is a great example of the application of low carbohydrate diets for obesity, with the intention of weight loss and improvement in cardiovascular risk (CV risk). A good CV risk predictor is the atherogenic index of plasma (AIP) calculated as log (TG/HDL [mmol]), which is strongly affected by serum triglycerides, which in turn is associated with the carbohydrate intake. This study determined the effect of the initial phase of Atkins diet program, consisting in 20 g/day of carbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 21 publications
0
9
1
Order By: Relevance
“…These findings were parallel with the results of the previous studies. [7][8][9][10][11][12][13]26,27 We additionally found that these lipid levels and atherogenic indices did not differ in lower-or higher-risk groups for exacerbation. Additionally, epidemiological data showed a strong relationship between air-flow limitation and cardiovascular disease.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…These findings were parallel with the results of the previous studies. [7][8][9][10][11][12][13]26,27 We additionally found that these lipid levels and atherogenic indices did not differ in lower-or higher-risk groups for exacerbation. Additionally, epidemiological data showed a strong relationship between air-flow limitation and cardiovascular disease.…”
Section: Discussionmentioning
confidence: 93%
“…In the past decade, in addition to classical atherogenic risk factors, it was described that increases in some lipid ratios called atherogenic indices yield advantages in identifying some individuals with chronic diseases at higher risk of developing cardiovascular disease. [7][8][9][10][11][12][13][14][15]25 To our knowledge, although atherogenic indices were studied to predict cardiovascular disease in some diseases, including diabetes mellitus, metabolic syndrome, systemic hypertension, familial Mediterranean fever, pregnancy-induced hy- pertension, psychiatric diseases, and others, its role in COPD had not been studied. [7][8][9][10][11][12][13]26,27 In the present study, we evaluated and compared atherogenic indices (atherogenic index of plasma, cardiogenic risk ratio, and atherogenic coefficient) in addition to the serum lipid parameters in subjects with COPD and in control subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 The uric acid level was significantly elevated by LCD, and the elevated degree was significantly correlated with HbA1c. From our clinical experience with the LCD diet in thousands of patients, the changes in uric acid levels ran the gamut from increase, stabilization and decrease.…”
mentioning
confidence: 89%
“…One of the dietary approaches that has attracted particular success in recent years is the “ketogenic diet” (KD). This is a dietary program that was designed in the 1920s as a therapy for drug-resistant epilepsy [ 1 , 2 ], which then gained popularity in the 1970s as a weight-loss diet (Atkins) [ 3 , 4 ]. Currently, there are many diets that are based on this model.…”
Section: Introductionmentioning
confidence: 99%